2021
DOI: 10.1051/0004-6361/202037494
|View full text |Cite
|
Sign up to set email alerts
|

Accreting protoplanets: Spectral signatures and magnitude of gas and dust extinction at Hα

Abstract: Context. Accreting planetary-mass objects have been detected at H α, but targeted searches have mainly resulted in non-detections. Accretion tracers in the planetary-mass regime could originate from the shock itself, making them particularly susceptible to extinction by the accreting material. High-resolution (R > 50 000) spectrographs operating at H α should soon enable one to study how the incoming material shapes the line profile. Aims. We calculate how much the gas and dust accreting onto a planet reduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 224 publications
(336 reference statements)
0
25
0
Order By: Relevance
“…They include the (disputed) candidate LkCa 15b: M p < 5 − 10M J , M M M 10 yr companions have been directly imaged at Hα, with recent surveys returning no new detections (Cugno et al 2019;Zurlo et al 2020). This may be a low Strehl selection effect (Close 2020) or a reflection of differences in accretion physics at planetary masses (Aoyama et al 2021;Marleau et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They include the (disputed) candidate LkCa 15b: M p < 5 − 10M J , M M M 10 yr companions have been directly imaged at Hα, with recent surveys returning no new detections (Cugno et al 2019;Zurlo et al 2020). This may be a low Strehl selection effect (Close 2020) or a reflection of differences in accretion physics at planetary masses (Aoyama et al 2021;Marleau et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While the preshock velocity is consistent with measured M  's and assumed mass (and radius; see Figure 13 of Aoyama et al 2020), the number density is higher than expected for the measured M  assuming a pure planetaryshock model. This could be explained by shock emission with a low filling factor resulting from a magnetospheric accretion flow, absorption in the postshock region (Hashimoto et al 2020), strong accretion column extinction (Marleau et al 2022, though they found that the M  is too low for absorption by either gas or dust in the accretion flow), or circumplanetary disk extinction in the line of sight (Aoyama et al 2020). High-resolution (R ∼ 10,000) spectra will help disentangle the accretion flow geometry and shed light on the nature of the accretion shock, as resolved line profiles can distinguish between geometries (Aoyama et al 2020;Marleau et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Adopting a line-of-sight extinction of = 0.5 mag (the same as the star, Garcia Lopez et al 2006) and assuming no additional extinction opacity, we find a H line luminosity of H = 2.2 ± 0.7 × 10 −5 ⊙ . At this H , gas in the accretion flow should not lead to significant absorption (Marleau et al 2022). The H value corresponds to a total accretion luminosity of log( acc ∕ ⊙ ) = −2.8 ± 0.3 by assuming the planetary surface shock model (Aoyama et al 2018;Aoyama et al 2021) or log( acc ∕ ⊙ ) = −3.5 ± 0.3 using the empirical relation for classic T Tauri stars (Alcalá et al 2017), respectively.…”
Section: Discussionmentioning
confidence: 99%